MEDIASI SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA PERBANKAN - Nahdhah Nahdhah (Badamai Law Journal, 2016)
The present research aims to understand the position of the banking mediation institution within the regulatory frameworkproduced by the state and by the Central Bank of Indonesia, and to explore the ways in which resolution of conflicts are mediated by the institution.This study approaches the topic using normative-juridical perspective. That is to research legal norms related to this issue by utilizing three different sources: primary, secondary and tertiary legal sources. In turn, relevant data will be proccessed and analyzed so that the research question will be properly answered.    It is a logical consequence of the independency of the Central Bank of Indonesia that the regulation of the Central Bank number 8/5/PBI/2006 on Banking Mediation was replaced by the regulation of the Central Bank number 10/1/PBI/2008. In the new regulation, there is no legal basis for the works of the banking mediation institution, which are highly important. This situasion of ‘legal vacuum’ needs some legal solutions, either by passing a relevant bill or producing a temporary operating regulation. Keywords: Alternative Dispute Resolution, Banking, MediationPenelitian ini bertujuan untuk memahami posisi lembaga mediasi perbankan dalam peraturan frameworkproduced oleh negara dan oleh Bank Indonesia, dan untuk mengeksplorasi cara-cara di mana resolusi konflik dimediasi oleh lembaga.Penelitian ini mendekati topik menggunakan perspektif normatif-yuridis. Itu adalah untuk penelitian norma-norma hukum yang terkait dengan masalah ini dengan memanfaatkan tiga sumber yang berbeda: sumber hukum primer, sekunder dan tersier. Pada gilirannya, data yang relevan akan diproses dan dianalisa sehingga pertanyaan penelitian akan dijawab dengan benar.Ini merupakan konsekuensi logis dari independensi Bank Sentral Indonesia bahwa regulasi jumlah Bank Sentral 05/08 / PBI / 2006 tentang Mediasi Perbankan digantikan oleh regulasi jumlah Bank Sentral 01/10 / PBI / 2008. Dalam peraturan baru, tidak ada dasar hukum bagi karya-karya dari lembaga mediasi perbankan, yang sangat penting. situasion ini 'kekosongan hukum' membutuhkan solusi hukum, baik dengan melewati tagihan yang relevan atau memproduksi peraturan operasi sementara.Kata kunci : Alternatif Penyelesaian Sengketa, Mediasi, Perbankan